Facile and scalable synthesis of topologically nanoengineered polypeptides with excellent antimicrobial activities. Issue 3 (11th December 2019) - Zhang, Yu; Song, Wenliang; Li, Shuwei; Kim, Dae-Kyoung; Kim, Jae Ho; Kim, Jung Rae; Kim, Il
Abstract : A facile and scalable strategy for the quick library synthesis of linear-, hinged-, star-, and cyclic-polypeptides with broad-spectrum antimicrobial activity has been reported. Abstract : A facile and scalable strategy for the quick library synthesis of linear-, hinged-, star-, and cyclic-polypeptides with broad-spectrum antimicrobial activity has been reported. The topologically nanoengineered polypeptides show superior antimicrobial activity against Gram-positive and Gram-negative bacteria and low toxicity, allowing screening of architectural polypeptides as mimics of host defense peptides for antimicrobials.